PENGEMBANGAN KOLEKSI JURNAL ELEKTRONIK DI PUSAT LAYANAN PUSTAKA UNIVERSITAS TERBUKA (PUSLATA UT) - Baharuddin, M. Arif; Rachman, Margareta (BACA: Jurnal Dokumentasi dan Informasi, 2017)
This research aims to see the development of the electronic journal collection at Puslata UT. This research used qualitative approach with descriptive method. Reviews these results indicate that Puslata UT has run a series of activities for the development of the electronic journal collection, but in fact the use of electronic journals by the academic society is very low. It happened because some temporary policies were not maximized and less inappropriate to fulfill information needs of academic society. Electronic journal more needed for the accreditation process and the study by researcher at UT center. The results of this research shows that PUSLATAUT should make a written policy or guidelines of the development of the electronic journal collection, and create a strategic plan so that electronic journals can reach some academic societies in some areas.